Raising Perceptions on Corporate Social Responsibility for Achieving Sustainable Development Goals - Pal, Subrata Kumer; Sarker, Pramath Chandra; Odhikari, Shibu Chandra (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The Sustainable Development Goals (SDGs) 2030 is the United Nations development agenda for developing the economy, society, and environment. Moreover, Corporate Social Responsibility (CSR) is an emerging topic in the business world. The paper aims to pursue business students’ knowledge and perception of CSR activities linked to SDGs. The quantitative research design and descriptive research analysis were used. The data were collected from business learning students of three public universities in Bangladesh. CSR’s perception-related items positively correlated with Spearman’s Rho’s formula. The descriptive statistics revealed perceptions of CSR activities among respondents, which are directly and indirectly related to SDGs. In addition, the two-tailed Mann-Whitney <em style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">U<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> test and Kruskal-Wallis <em style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">H<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> test showed a variation of perceptions among groups. The findings of this study showed respondents had an acceptable knowledge level on CSR activities. There was a positive perception of respondents on economic and social dimensions of SDGs and mainly included in philanthropic and economic fields of CSR. Besides, their consciousness of the environmental dimension related to ethical and legal activities of CSR concepts was comparatively low. Finally, favourable knowledge and perception of business studying students in CSR activities are imperative for the successful implementation of SDGs.